ANALISIS STRUKTUR BATIN PUISI SURAT DARI IBU KARYA ASRUL SANI - Sandi Nurjaman (IKIP Siliwangi, 2022)
Literary work is a form of artistic expression from the author which is poured through the medium of language. The form of expressive expression in literary works is a depiction of life that contains aesthetics and the value of life. Poetry which is part of a literary work is composed of a series of words and content of a literary work, the arch was motivated by the researcher's curiosity about the poetry of Asrul Sani. Through the poem “Surat from Mother”, Asrul Sani crystallizes a message of life that is deposited in lines and stanzas. The analysis carried out in this study is to determine the inner structure of the poem. The purpose of this research is to describe the inner structure of poetry such as theme, tone and feeling, atmosphere, and message. The method prepared by the researcher is descriptive qualitative. The results of the analysis can be concluded that this poem has the theme of love, struggle, and longing. The feelings and atmosphere described are emotion, sadness, and pride. The message is that we should be devoted to parents, especially mothers who have sacrificed a lot for the success and happiness of their children.